CONTINUITY OF CARE FOR PREGNANT WOMEN WITH MILD ANEMIA AT THE SERASI PRATAMA CLINIC, MEDAN HELVETIA DISTRICT, MEDAN CITY, NORTH SUMATERA PROVINCE 2025 - Pasaribu, Lamtiar; Ribur Sinaga; Sri Muliana Putri Bakara; Rosmey Linda Bololo; Delyunmas Mohof; Ernawati; Siti Sabbiah (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Anemia in pregnancy is a condition characterized by decreased hemoglobin (Hb) levels in the blood of pregnant women. Mild anemia is usually characterized by Hb levels between 9–10.9 g/dL. This condition often occurs due to increased iron requirements during pregnancy that are not balanced by adequate intake. Several factors contributing to low awareness of anemia in pregnant women include limited access to accurate information, varying levels of education, and dietary habits that do not meet nutritional needs during pregnancy. Furthermore, nausea and vomiting, often experienced in the first trimester of pregnancy, are also major reasons mothers are reluctant to consume nutritious foods and iron supplements. Therefore, more interactive and easy-to-understand educational methods are needed so that pregnant women can adopt a healthy lifestyle during pregnancy. Pregnant women are required to regulate their diet to meet nutritional needs. A balanced diet consists of appropriate amounts and proportions of carbohydrates, protein, minerals, vegetables, and vitamins to meet the needs of the body. (Delfina et al., 2024)